ppGpp binding to a site at the RNAP-DksA interface accounts for its dramatic effects on transcription initiation during the stringent response - Ross, Wilma (Mol Cell, 2016)
Throughout the bacterial domain, the alarmone ppGpp dramatically reprograms transcription following nutrient limitation. This “stringent response” is critical for survival and antibiotic-tolerance and is a model for transcriptional regulation by small ligands. We report that ppGpp binds to two distinct sites 60 angstroms apart on E. coli RNA polymerase (RNAP), one characterized previously (Site 1) and a second identified here at an interface of RNAP and the transcription factor DksA (Site 2). The location and unusual tripartite nature of Site 2 account for the DksA-ppGpp synergism and suggest mechanisms for ppGpp enhancement of DksA’s effects on RNAP. Site 2 binding results in the majority of ppGpp’s effects on transcription initiation in vitro and in vivo, and strains lacking Site 2 are severely impaired for growth following nutritional shifts. Filling of the two sites at different ppGpp concentrations would expand the dynamic range of cellular responses to changes in ppGpp levels.